Herbarium data: Global biodiversity and societal botanical needs for novel research. (28th February 2018) - James, Shelley A.; Soltis, Pamela S.; Belbin, Lee; Chapman, Arthur D.; Nelson, Gil; Paul, Deborah L.; Collins, Matthew
Abstract : Building on centuries of research based on herbarium specimens gathered through time and around the globe, a new era of discovery, synthesis, and prediction using digitized collections data has begun. This paper provides an overview of how aggregated, open access botanical and associated biological, environmental, and ecological data sets, from genes to the ecosystem, can be used to document the impacts of global change on communities, organisms, and society; predict future impacts; and help to drive the remediation of change. Advocacy for botanical collections and their expansion is needed, including ongoing digitization and online publishing. The addition of non‐traditional digitized data fields, user annotation capability, and born‐digital field data collection enables the rapid access of rich, digitally available data sets for research, education, informed decision‐making, and other scholarly and creative activities. Researchers are receiving enormous benefits from data aggregators including the Global Biodiversity Information Facility (GBIF), Integrated Digitized Biocollections (iDigBio), the Atlas of Living Australia (ALA), and the Biodiversity Heritage Library (BHL), but effective collaboration around data infrastructures is needed when working with large and disparate data sets. Tools for data discovery, visualization, analysis, and skills training are increasingly important for inspiring novel research that improves the intrinsic value of physical and digital botanical collections.